On the development of methods for measuring vibration of building structures - Gusev, G.N.; Epin, V.V.; Tsvetkov, R.V.; Shestakov, A.P. (Perm Federal Research Centre Journal, 2024)
Vibration processes contain useful information about the properties of both the signal source and the medium in which they propagate. Control of vibration parameters of structures is an integral part of monitoring. There are various methods and means of measuring vibration processes in building structures, as well as their registration. The development of technology and electronics allows us to steadily improve the parameters of vibration sensors, reduce their dimensions and create fundamentally new sensitive elements. Examples are given of vibration measuring equipment used by the staff of the Institute of Continuous Media Mechanics for testing large-scale building structures over the past 25 years. The results of vibration measurements of large-scale structures are shown, as well as the evolution of the natural frequency of a building structure during its long-term monitoring.